F = kq2 / r2
q = ne
F = k(ne)2 / r2
n = âš(r2F / ke2) = (r/e) âš(F/k)
k = 9 x 109 Nm2/C2
e = 1.6 x 10-19 C
n = [(4.2 x 10-10) / (1.6 x 10-19)] âš[(5.2 x 10-9) / (9 x 109)] ≅ 1.995 ≅ 2
Answer:
a3+13a
Step-by-step explanation:
sorry I don't know how to solve this
Answer:
c=3
Step-by-step explanation:
do u need the explanation?
Hey! Sorry for the 6 day late response. The answer is:
25%
<span>(f o g)(4) = f(g(4))
so
g(4) = </span><span>-2(4) -6 = -14
</span>f(g(4)) = <span>3(-14) -7 = -49
answer
</span><span> (f o g)(4) = -49</span>